2016
DOI: 10.1177/1049909116643927
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Fluconazole Therapy for Oral Thrush in Hospice and Palliative Medicine Patients

Abstract: Single-dose fluconazole 150 mg is an effective treatment of oral thrush for individuals with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Functional impact include difficulties in swallowing, speaking and eating, food restriction, sense of oral dryness and pain, which resulted in lack of food enjoyment [5,26,28]. Table 4 presents our findings on the management of some oral conditions among palliative patients and their effectiveness [11,15,17,[19][20][21][22][23] Our study revealed that the common management options for xerostomia are drug and medical treatments [15], lubricating lips and mucosa [17], acupuncture [19], and standard oral care which improved dry mouth (in 80% or more) of the patients [11]. For candidiasis, a single-dose fluconazole 150 mg via mouth was found to be very effective as the symptoms decreased significantly (P < 0.001) in most patients [20], and local antifungal treatments were reported to be efficacious in 78.1% of the patients [23].…”
Section: Common Oral Conditions Among Palliative Patientsmentioning
confidence: 95%
See 3 more Smart Citations
“…Functional impact include difficulties in swallowing, speaking and eating, food restriction, sense of oral dryness and pain, which resulted in lack of food enjoyment [5,26,28]. Table 4 presents our findings on the management of some oral conditions among palliative patients and their effectiveness [11,15,17,[19][20][21][22][23] Our study revealed that the common management options for xerostomia are drug and medical treatments [15], lubricating lips and mucosa [17], acupuncture [19], and standard oral care which improved dry mouth (in 80% or more) of the patients [11]. For candidiasis, a single-dose fluconazole 150 mg via mouth was found to be very effective as the symptoms decreased significantly (P < 0.001) in most patients [20], and local antifungal treatments were reported to be efficacious in 78.1% of the patients [23].…”
Section: Common Oral Conditions Among Palliative Patientsmentioning
confidence: 95%
“…Studies reporting on oral conditions among palliative patients are summarized in Table 1. Of the included studies, 16 were quantitative studies [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], and 3 were qualitative studies [25][26][27] (Table 2).…”
Section: Characteristics Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…contact with lesions) and (g) patient adherence. (Currently, there is no robust evidence to support the use of single doses of fluconazole in this condition [81] (no guideline possible)).…”
Section: Managementmentioning
confidence: 99%